Illumination of the Problems of Globalization in the Story "Ozor" by Isajan Sultan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In recent years, Isajon Sultan is one of our writers who has been paying attention to the wide coverage of the problems of globalization in his works. When analyzing his stories such as "An Eight-Year-Old Boy of the Twentieth Century", "Marriage", they are distinguished by the relevance of the topic, the vitality of the events reflected in it, and their unique style.